Antioxidant effect of mesalazine in the experimental colitis model induced by acetic acid - Moura, Rosa Maria; Hartmann, Renata Minuzzo; Licks, Francielli; Schemitt, Elizângela Gonçalves; Colares, Josieli Raskopf; do Couto Soares, Mariana; Fillmann, Lucio Sarubbi; Fillmann, Henrique Sarubbi; Marroni, Norma Possa (Journal of Coloproctology, 2016)
Introduction Inflammatory bowel disease (IBD) is characterized by a chronic inflammation of the gastrointestinal tract, without specific cause or pathogen.Objective The effect of mesalazine in a colitis model induced by acetic acid (AA) was evaluated.Methods We used 40 Wistar rats, ±350 g, divided into 4 groups: control (CO); control + mesalazine (CO + M); colitis (CL) and colitis + M (CL + M) at 24 and 48 h of treatment. The animals received the substances by an intracolonic enema of AA 4% and treatment with mesalazine PO 20 mg/kg after colitis induction.Results Mesalazine reduced tissue damage in the gut, normalized sphincter anal pressure levels and decreased lipid peroxidation, metabolites of nitric oxide and iNOS and NF-kB expression in the treated groups in both treatment time points (24 and 48 h), as well as the activity of antioxidant enzymes.Conclusion Mesalazine was effective in reducing tissue damage and oxidative and inflammatory damage, restored antioxidant capacity and increased anal sphincter pressure levels, possibly due to its antioxidant effect.
Keywords: Oxidative stress; Inflammation; Nitric oxide